2020
DOI: 10.1101/2020.12.21.20248610
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Population risk factors for severe disease and mortality in COVID-19: A global systematic review and meta-analysis

Abstract: AimCOVID-19 clinical presentation is heterogeneous, ranging from asymptomatic to severe cases. While there are a number of early publications relating to risk factors for COVID-19 infection, low sample size and heterogeneity in study design impacted consolidation of early findings. There is a pressing need to identify the factors which predispose patients to severe cases of COVID-19. For rapid and widespread risk stratification, these factors should be easily obtainable, inexpensive, and avoid invasive clinica… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
50
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 106 publications
8
50
1
1
Order By: Relevance
“…While research on COVID-19 is rapidly evolving, it is well established that age 23 and obesity 24 are significant variables. In the data-driven model, we found that age was the most critical factor in determining outcome, in line with meta-analyses on outcomes in COVID-19 patients 10,23 . Obesity is also well reflected in our model, with body mass index (BMI) and related measures featuring dominantly in the data-driven ranking.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…While research on COVID-19 is rapidly evolving, it is well established that age 23 and obesity 24 are significant variables. In the data-driven model, we found that age was the most critical factor in determining outcome, in line with meta-analyses on outcomes in COVID-19 patients 10,23 . Obesity is also well reflected in our model, with body mass index (BMI) and related measures featuring dominantly in the data-driven ranking.…”
Section: Discussionsupporting
confidence: 79%
“…While both conditions are linked to obesity, diabetes has been reported to confer significant independent mortality risk 27 . Evidence for the role of hypertension as an independent risk factor, however, is not fully established, with meta-analyses finding hypertension non-significant after adjusting for other risk factors 10,28,29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnant women are a vulnerable group in this pandemic, with an increased risk for severe disease and adverse outcomes if infected, including preterm birth, venous thromboembolism, severe respiratory complications requiring invasive ventilation. (9)(10)(11)(12) Lactating mothers could also potentially infect the infant postnatally via droplet infection. (13,14) Despite the benefits of vaccination to prevent maternal and fetal complications, studies have demonstrated varying rates of vaccine acceptance in pregnant and lactating women.…”
Section: Introductionmentioning
confidence: 99%
“…The SARS-CoV-2 pandemic has resulted in over 2.8 million deaths to date and the most significant determinant of outcome is age at the time of primary infection (Booth, Reed et al 2021). In children, SARS-CoV-2 infection is generally asymptomatic or mild and contrasts with high rates of hospitalisations and deaths among older adults (Viner, Mytton et al 2021).…”
Section: Introductionmentioning
confidence: 99%